METODE PEMBELAJARAN TARI DALAM PKM DOSEN ISI SURAKARTA DI SMK NEGERI 8 SURAKARTA - Saryuni Padminingsih (Institut Seni Indonesia Surakarta, 2016)
Art teacher, in fact, is most needed in schools today for they have to increase quality of the arts studies so that they must recruit the professional art teachers. For the reason, the writer would like to hold community service in SMK 8 Surakarta. The writer uses the method of teaching and training. Teaching method is used to give informations about material completely, while training method is executed to applicate the theory. The result of this community service is a model of dance learning which is suited to the school needs.Key words: art teacher, method, learning